Vicarious pain while observing another in pain: an experimental approach - Vandenbroucke, Sophie; Crombez, Geert; Van Ryckeghem, Dimitri; Brass, Marcel; Van Damme, Stefaan; Goubert, Liesbet (Frontiers in Human Neuroscience, 2013)
Objective: This study aimed at developing an experimental paradigm to assess vicarious pain experiences. We further explored the putative moderating role of observer’s characteristics such as hypervigilance for pain and dispositional empathy. Methods: Two experiments are reported using a similar procedure. Undergraduate students were selected based upon whether they reported vicarious pain in daily life, and categorized into a pain responder group or a comparison group. Participants were presented a series of videos showing hands being pricked whilst receiving occasionally pricking (electrocutaneous) stimuli themselves. In congruent trials, pricking and visual stimuli were applied to the same spatial location. In incongruent trials, pricking and visual stimuli were in the opposite spatial location. Participants were required to report on which location they felt a pricking sensation. Of primary interest was the effect of viewing another in pain upon vicarious pain errors, i.e., the number of trials in which an illusionary sensation was reported. Furthermore, we explored the effect of individual differences in hypervigilance to pain, dispositional empathy and the rubber hand illusion (RHI) upon vicarious pain errors. Results: Results of both experiments indicated that the number of vicarious pain errors was overall low. In line with expectations, the number of vicarious pain errors was higher in the pain responder group than in the comparison group. Self-reported hypervigilance for pain lowered the probability of reporting vicarious pain errors in the pain responder group, but dispositional empathy and the RHI did not. Conclusion: Our paradigm allows measuring vicarious pain experiences in students. However, the prevalence of vicarious experiences of pain is low, and only a small percentage of participants display the phenomenon. It remains however unknown which variables affect its occurrence.